Directed modification of β-mannanase substrate affinity based on rational design - Wei Xihuan; Wang Chunjuan; Zhao Mei; Li Jianfang; Wu Minchen (浙江大学学报. 农业与生命科学版)
β-mannanases (endo-β-1, 4-D-mannanases, EC 3.2.1.78), which exist widely in various organisms especially in microorganisms, can catalyze the cleavage of internal β-1, 4-D-mannosidic linkages of mannan backbones. To date, almost all known β-mannanases have been classified into glycoside hydrolase (GH) families 5, 26 and 113 based on their amino acid sequence alignment and hydrophobic cluster analysis. Recently, they have attracted much attention due to their great potential applications in industrial processes, such as bioleaching pulps, depolymerizing ant-i nutritional factors in feedstuffs, extracting oils from leguminous seeds, hydrolyzing mannanbased polymers in hydraulic fracturing of oil and gas wells, and producing mannooligosaccharides. However, most of commercial β-mannanases had some shortages in enzymatic properties, such as lower substrate affinity and poorer tolerance to extreme environments, which hindered the development of β-mannanases.A GH family 5 β-mannanase (AuMan5A) from Aspergillus usamii YL-01-78 was used as the object of this study. The directed modification for its substrate affinity was subjected to the rational design and site-directed mutagenesis to gain a mutant enzyme AuMan5AY111F with higher affinity. Firstly, the three-dimensional (3-D) structure of a docked complex of Auman5A with mannobiose was predicted through homology modeling and molecular docking simulation. On the basis of this 3-D structure, 38 amino acid sites in proximity to mannobiose within 8 Å were located by using the PyMol software. Secondly, the multiple alignment of various β-mannanase sequences was performed, among which each sequence shared more than 50% identity with AuMan5A. According to the properties of amino acids at 17 non-conserved sites and their locations on the 3-D structure of AuMan5A, Tyr111, Phe206 and Tyr243 were selected to be substituted with the similar amino acids and/or high frequency ones in other β-mannanase sequences, respectively, forming a series of mutant enzymes. Lastly, binding free energies (ΔGbind) of various β-mannanases with mannobiose were calculated by using the molecular mechanics Poisson- Boltzmann surface area (MM-PBSA) method, respectively. The ΔGbind of AuMan5AY111F was - 237.7 kJ/mol, lower than those of other enzymes. Based on the rational design, an AuMan5AY111F-encoding gene, Auman5AY111F, was constructed by mutating a Tyr111-encoding codon (TAC) of the Auman5A into a Phe111-encoding TTC by megaprimer PCR. Then, the Auman5AY111F and Auman5A were expressed in Pichia pastoris GS115, and kinetic parameters of the purified recombinant AuMan5AY111F and AuMan5A (reAuMan5AY111F and reAuMan5A) were determined, respectively. The results displayed that the Km value of reAuMan5AY111F, towards guar gum, dropped to 2.5 mg/mL from 3.9 mg/mL of reAuMan5A, indicating the substrate affinity of reAuMan5A increased correspondingly. While, the Vmax value of reAuMan5A kept almost unchanged after site-directed mutagenesis.The directed modification of AuMan5A based on the rational design for enhancing its substrate affinity was firstly predicted by using various bioinformatics softwares, and then was confirmed by site-directed mutagenesis. This work provides a novel technology strategy for the directed modification of substrate affinities of β-mannanases and other enzymes.